Combretastatin A4 Nanodrug‐Induced MMP9 Amplification Boosts Tumor‐Selective Release of Doxorubicin Prodrug. Issue 44 (24th September 2019) - Jiang, Jian; Shen, Na; Ci, Tianyuan; Tang, Zhaohui; Gu, Zhen; Li, Gao; Chen, Xuesi
Abstract: Tumor‐associated enzyme‐activated prodrugs can potentially improve the selectivity of chemotherapeutics. However, the paucity of tumor‐associated enzymes which are essential for prodrug activation usually limits the antitumor potency. A cooperative strategy that utilizes combretastatin A4 nanodrug (CA4‐NPs) and matrix metalloproteinase 9 (MMP9)‐activated doxorubicin prodrug (MMP9‐DOX‐NPs) is developed. CA4 is a typical vascular disrupting agent that can selectively disrupt immature tumor blood vessels and exacerbate the tumor hypoxia state. After treatment with CA4‐NPs, MMP9 expression can be significantly enhanced by 5.6‐fold in treated tumors, which further boosts tumor‐selective active drug release of MMP9‐DOX‐NPs by 3.7‐fold in an orthotopic 4T1 mammary adenocarcinoma mouse model. The sequential delivery of CA4‐NPs and MMP9‐DOX‐NPs exhibits enhanced antitumor efficacy with reduced systemic toxicity compared with the noncooperative controls. Abstract : The paucity of enzymes within tumors inhibits activation of tumor‐associated enzyme‐activated prodrugs. It is demonstrated that combretastatin A4 nanodrug can selectively induce matrix metalloproteinase 9 signal amplification in treated tumors, boosting tumor‐selective activated drug release of matrix metalloproteinase‐activated doxorubicin prodrug nanomedicine.